VISION SYSTEM DEVELOPMENT IN ECCENTRICITY TESTING FOR KWH METER UPPER BEARING - Emilham Mirshad (Widyariset, 2018)
Eccentricity measurement techniques are developed to ensure optimization of operational works, either for large or small objects such as upper bearing kWH meter. Small object eccentricity testing has been done by using precise and sensitive touch trigger probing and a special sofware that makes it expensive. This study developed a more economical vision systemin eccentricity testing. It consists of bearing holder and CCD microscope as an image recorder and computerized image processing. It uses three tested bearing during image recording process, which obtained 12 images from each tested bearing taken from every 30o angle, and one image as registration reference. Image registration process is conducted to correct imperfections bearing mounting into its holder and use centroid method to test the eccentricity of upper bearing kWH meter. This study is succeed in making an eccentricity testing prototype of upper bearing kWH meter which obtained result of 2nd bearing has its largest standard deviation. From all standard deviation value obtained that x -axis (horizontal) standard deviation is larger than y-axis (vertical) which means that detection of x direction is more accurate than y direction. To enhance precision image acquisition in the next study, it is expected the use of a computer system with homogeneous illumination is enabled.